Contribution of wetland resources to household food security in Uganda - Turyahabwe, Nelson; Kakuru, Willy; Tweheyo, Mnason; Mwesigye Tumusiime, David (Agriculture & Food Security, 2013)
In Uganda, nearly 1.4 million people are currently food insecure, with the prevalence of food energy deficiency at the country level standing at 37%. Local farmers are vulnerable to starvation in times of environmental stress, drought and floods because of dependence on rain-fed agriculture. Accordingly, the farmer’s means of increasing food production has always been an expansion of area under cultivation from virgin and fragile areas, especially wetlands. Consequently, Uganda has lost about 11,268 km2 of wetland, representing a loss of 30% of the country’s wetlands from 1994 to 2009. While the environmental importance of wetland ecosystems is widely recognized, their contribution to household food security is still hardly explored. In this paper an assessment of the contribution of wetland resources to household food security and factors influencing use of wetland resources in Uganda are reported. Methods: A number of livelihood tools in food security assessment including focus group discussions, key informant interviews, direct observations and a household questionnaire survey, were used to collect the data. A total of 247 respondents from areas adjacent to wetlands were involved in the household questionnaire survey conducted in three agro-ecological zones that are frequently characterized as food insecure. Results: The findings indicate that about 83% of the households experienced food insecurity. The main indicators of food insecurity were low harvest (30.9%) and when people buy locally grown food items (18%). Most households felt food secure when they had perennial crops (43.2%) in their gardens, or adequate money to buy food (23.9%). The prevalence of food insecurity was significantly lower among households with older and better educated household heads, but also among households located in Lake Victoria Crescent and South western farmlands agroecological zones, but significantly higher among households that were female headed, larger and participate in collection of wetland resources. Over 80% of the respondents reported that wetland resources provide products and services that contribute enormously to their household food security. Besides, they also indirectly contribute to food security by providing services that foster food production such as weather modifications and nutrient retention. Households with older heads and those that reside in the Lake Victoria Crescent agro-ecological zone when compared to counterparts in the Lake Kyoga agro-ecological zone are more likely to have a higher dependence on wetlands for food security. Conclusions: With increasing population around the wetlands, coupled with land shortage and weather variations, households with limited options will continue to generally rely on wetlands for food security and income for sustaining their livelihoods unless alternative livelihood options are provided. There is thus a need to design appropriate food production technologies that ensure sustainable use of wetland resources for food security.
Keywords: Food security; Food insecurity; Wetland management; Wetland resources; Uganda